BONEKA TAWARAJA (CERITA WAYANG BERIRAMA JARI): MEDIA PEMBELAJARAN BAHASA INDONESIA DALAM PENINGKATAN PENDIDIKAN KARAKTER - Ismawarsari, Fetiyani Yuniana; Indradini, Risa Hafida; Hidayat, Puji Nur (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
The research objectives are (1) to find out how Tawaraja dolls are used for storytelling and (2) to reveal the effectiveness of Tawaraja dolls used for puppet storytelling and (3) to improve character education. The research was conducted in the Bahasa Indonesia class in Bantul Timur Elementary School and the subjects were the grade VB students. The method is research and development. This model is adopted from Borg and Gall’s theory. The steps are information collecting, planning, developing a preliminary form of product, preliminary field testing, revising the main product, main field testing, conducting operational product revision, operational field testing, revising the final product revision, and conducting dissemination and implementation (Ghufron, 2005: 8). The result is the product of Tawaraja dolls as learning media which are effective in developing the students’ character.